The Influence of Inflation, Exchange Rate, Non Performing Financing (NPF) and Financing to Deposit Ratio (FDR) to Financial Sustainability Ratio with Return on Aset (ROA) as Mediation - Ali Fanisa Himawan; Imanda Firmantyas Putri Pertiwi (Accounting and Finance Studies, 2022)
ABSTRACT The background of this research is that banks as one of the supporters of the Indonesian economy are required to experience financial sustainability. The FSR ratio is used to determine the growth of a bank and to determine whether the bank is capable or not in continuing its financial performance. The purpose of this study was to determine the effect of inflation, exchange rates, NPF and FDR on FSR at Islamic Commercial Banks in Indonesia in 2016-2020 with ROA as a mediating variable. This research is classified as a quantitative research with a population of 14 BUS registered at OJK. The research sample was determined by purposive sampling method with specified criteria so that there were 13 samples used. Then 65 data were obtained from the 13 samples in the 2016-2020 observation period. The type of data used is secondary data. The analytical method used is multiple linear regression analysis with PLS test using Eviews 10 software. The results show that partially the inflation, exchange rate and FDR variables have no effect on the FSR of Islamic banks. The NPF variable has a negative and significant effect on FSR. And the ROA variable has a positive and significant effect on FSR. The results also show that the variables of inflation, exchange rate, and FDR have no effect on ROA. While the NPF variable has a negative and significant effect on ROA. According to the research results, ROA is only able to mediate the effect of NPF on FSR. ABSTRACTThe background of this research is that banks as one of the supporters of the Indonesian economy are required to experience financial sustainability. The FSR ratio is used to determine the growth of a bank and to determine whether the bank is capable or not in continuing its financial performance. The purpose of this study was to determine the effect of inflation, exchange rates, NPF and FDR on FSR at Islamic Commercial Banks in Indonesia in 2016-2020 with ROA as a mediating variable. This research is classified as a quantitative research with a population of 14 BUS registered at OJK. The research sample was determined by purposive sampling method with specified criteria so that there were 13 samples used. Then 65 data were obtained from the 13 samples in the 2016-2020 observation period. The type of data used is secondary data. The analytical method used is multiple linear regression analysis with PLS test using Eviews 10 software. The results show that partially the inflation, exchange rate and FDR variables have no effect on the FSR of Islamic banks. The NPF variable has a negative and significant effect on FSR. And the ROA variable has a positive and significant effect on FSR. The results also show that the variables of inflation, exchange rate, and FDR have no effect on ROA. While the NPF variable has a negative and significant effect on ROA. According to the research results, ROA is only able to mediate the effect of NPF on FSR.